IMPROVING MATHEMATICAL LEARNING OUTCOMES IN SIMPLE SPLIT MATERIALS THROUGH CONCRETE OBJECTS - Nining Nurasiyah; Iim Iim; Siti Ruqoyyah (COLLASE (Creative of Learning Students Elementary Education), 2018)
The background of this study is because the learning process that has not been maximized and students' learning achievement about simple fractions is still relatively low. The purpose of this study was to determine the extent to which the use of concrete object props can improve the learning outcomes of third grade elementary school students in mathematics subjects in simple fractions. The method in this study, using Classroom Action Research. Classroom Action Research conducted in 2 cycles, each cycle has 4 stages. Data collection techniques used are observation, questionnaire, test, and attitude scale. The subjects in this study were 30 students of class III SD Islam Mutiara Hati, District of Antapani Tengah, Bandung. Based on the results of the study, the researchers concluded that the use of concrete object props in simple fraction materials can improve student learning outcomes and activeness as well as students' responses to learning are quite positive.